Changes in human brain glutamate concentration during hypoglycemia: insights into cerebral adaptations in hypoglycemia-associated autonomic failure in type 1 diabetes - Terpstra, Melissa (Nature Publishing Group, 2014)
Hypoglycemia-associated autonomic failure (HAAF) is a condition in which patients with type 1 diabetes (T1D) who experience frequent hypoglycemia develop defective glucose counter-regulation and become unable to sense hypoglycemia. Brain glutamate may be involved in the mechanism of HAAF. The goal of this study was to follow the human brain glutamate concentration during experimentally induced hypoglycemia in subjects with and without HAAF. (1)H magnetic resonance spectroscopy was used to track the occipital cortex glutamate concentration throughout a euglycemic clamp followed immediately by a hypoglycemic clamp. T1D patients with HAAF were studied in comparison to two control groups, i.e., T1D patients without HAAF and healthy controls (n=5 per group). Human brain glutamate concentration decreased (P⩽0.01) after the initiation of hypoglycemia in the two control groups, but a smaller trend toward a decrease in patients with HAAF did not reach significance (P>0.05). These findings are consistent with a metabolic adaptation in HAAF to provide higher glucose and/or alternative fuel to the brain, eliminating the need to oxidize glutamate. In an exploratory analysis, we detected additional metabolite changes in response to hypoglycemia in the T1D patient without HAAF control group, namely, increased aspartate and decreased lactate.